Social transformation of solo city, indonesia: from the stigma of radicalism to the emergence of moderate islamic identity - Haqqi, Halifa; Cipto, Bambang; Qodir, Zuly; Ikhwan, Hakimul (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Surakarta City has long been associated with religious radicalism, positioning it as a critical site for studying Islamic moderation in Indonesia. This study aims to explore how religious communities in Surakarta construct and negotiate a moderate Islamic identity through the use of symbols and narratives, in response to stigmatization as a center of extremism. Employing a qualitative approach, data were collected through in-depth interviews with nine religious leaders from various organizations, participatory observations, and analysis of religious documents and local media. Thematic coding and triangulation techniques were used to ensure analytical rigor and validity. The findings reveal that symbols such as traditional attire, inclusive religious rituals, and narratives rooted in local Islamic history are strategically mobilized to promote a peaceful and nationalist version of Islam. These symbolic strategies serve not only to legitimize the presence of moderate communities in public space but also to resist and counter radical stereotypes. The study demonstrates that Islamic moderation at the local level emerges through complex, deliberate cultural processes rather than passive adaptation. It contributes to the discourse on community-based religious moderation and provides empirical insights for culturally grounded deradicalization policies.